Analisis Persediaan Drill Pipe dengan Pendekatan Economic Order Quantity (EOQ) pada Warehouse PT. XYZ - Syapolly, Dhea Ananda Novithalia Ardhany; Andrianti, Irma; Parji, Parji (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Inventory is goods reserved for a specific purpose. PT.XYZ certainly holds supplies of the materials they have. This research aims to calculate the economic order quantity, optimal order frequency, safety stock, and reorder point of existing drill pipe inventory at PT.XYZ using the Economic Order Quantity (EOQ) method. The results of this research are that companies should place orders for 3 ½" drill pipes: with a total of 983 joints, 4" drill pipes with a total of 967 joints, and 5" drill pipes with a total of 134 joints for economical orders. Then, companies should also place orders for 3 ½" drill pipes: 8 times, 4" drill pipes 8 times, and 5" drill pipes 6 times for optimal ordering frequency. Apart from that, companies should carry out safety stock on 3 ½" drill pipes with 375 joints, 4" drill pipes with 112 joints, and 5" drill pipes with 15 joints